A novel synthetic analogue of ω‐3 17, 18‐epoxyeicosatetraenoic acid activates TNF receptor‐1/ASK1/JNK signaling to promote apoptosis in human breast cancer cells. Issue 12 (10th August 2017) - Dyari, Herryawan Ryadi Eziwar; Rawling, Tristan; Chen, Yongjuan; Sudarmana, William; Bourget, Kirsi; Dwyer, Julie M.; Allison, Sarah E.; Murray, Michael
ABSTRACT: A saturated analog of the cytochrome P450–mediated ω‐3‐17, 18‐epoxide of ω‐3‐eicosapentaenoic acid (C20E) activated apoptosis in human triple‐negative MDA‐MB‐231 breast cancer cells. This study evaluated the apoptotic mechanism of C20E. Increased cytosolic cytochrome c expression and altered expression of pro‐ and antiapoptotic B‐cell lymphoma‐2 proteins indicated activation of the mitochondrial pathway. Caspase‐3 activation by C20E was prevented by pharmacological inhibition and silencing of the JNK and p38 MAP kinases (MAPK), upstream MAPK kinases MKK4 and MKK7, and the upstream MAPK kinase kinase apoptosis signal‐regulating kinase 1 (ASK1). Silencing of the death receptor TNF receptor 1 (TNFR1), but not Fas, DR4, or DR5, and the adapters TRADD and TNF receptor–associated factor 2, but not Fas‐associated death domain, prevented C20E‐mediated apoptosis. B‐cell lymphoma‐2 homology 3–interacting domain death agonist (Bid) cleavage by JNK/p38 MAPK linked the extrinsic and mitochondrial pathways of apoptosis. In further studies, an antibody against the extracellular domain of TNFR1 prevented apoptosis by TNF‐α but not C20E. These findings suggest that C20E acts intracellularly at TNFR1 to activate ASK1‐MKK4/7‐JNK/p38 MAPK signaling and to promote Bid‐dependent mitochondrial disruption and apoptosis. In in vivo studies, tumors isolated from C20E‐treated nu/nu mice carrying MDA‐MB‐231 xenografts showed increased TUNEL staining and decreased Ki67 staining, reflecting increased apoptosis and decreased proliferation, respectively. ω‐3‐Epoxy fatty acids like C20E could be incorporated into treatments for triple‐negative breast cancers.—Dyari, H. R. E., Rawling, T., Chen, Y., Sudarmana, W., Bourget, K., Dwyer, J. M., Allison, S. E., Murray, M. A novel synthetic analogue of ω‐317, 18‐epoxyeicosatetraenoic acid activates TNF receptor‐1/ASK1/JNK signaling to promote apoptosis in human breast cancer cells. FASEB J. 31, 5246−5257 (2017). www.fasebj.org